Borax as a Non-Food Grade Addivite in the Perspective of Foof Safety and Human Resources Formation: A Literature Review - Yunita Satya Pratiwi; Dina Mustika Rini; Hadi Munarko; Hadi Prayitno; Ristya Widi Endah Yani; Nadia Shoukat; Kaleem Ahmad (Future Science)
Many foodborne disease cases are still existing in Indonesia and worldwide. Chemicals that act as non-food grade additives is one of the cause. Borax is a chemical which still widely used for food in the community. The purpose of writing this scientific article is to analyze the impact of using borax as a non-food grade additive from the perspective of food safety and human resource formation. This article was based on scientific phenomena that occurred in studies conducted by the author in private, which was then analyzed more deeply based on a study of theories. As mentioned in government law, the use of borax for food additives is prohibited. However, borax is still widely used as food additives in the communities. This phenomenon is a threat to the assurance of food security for individuals and society, which in turn will have an impact on the output quality of human resources needed as the subject of future development. Several studies, investigated the negative effects of borax on the biological function of living things, showed that the use of borax significantly affects food safety in terms of human resources formation. Therefore, it needs both a preventive and curative solution for individuals, groups, and the government in an integrated manner. The use of borax in food is a threat to the assurance of food safety for individuals and society, which in turn will affect the quality of human resources so that a preventive and curative solution is needed.